Visual Analysis of Correlation Between Diseases Evolution and Human Dynamics - Lanyun Zhang; Hongyu Jiang; Weixin Zhao (JOIV : International Journal on Informatics Visualization, 2019)
With the urbanization and the increasing pervasiveness of medical system, the systems utilizing digital technologies for their operation generates enormous amounts of digital traces capable of reflecting in real-time human behaviors and health situation in the city. It is not only transforming how we study the urbanization effect on disease’s emergence and spread in cities but opens up new possibilities for tools that give people access to up-to-date information about urban dynamics the situation of diseases. Moreover, it was allowing us to make decisions that are more in sync with their environment. This paper introduces a prototype for exploring the dynamic of diseases-urbanization and supports urban planner meaningful access to large amounts of data capable of informing their decisions. We describe the technology context in this project, illustrate the requirements and the architecture of the platform to serve as a base for monitoring the health situation of the city. Finally, we shows the validity and practicability of the system by using real data in M city, China, which including electronic medical record, cellular network data, public transport, Census data.